Karakteristik Struktur Morfologi Ikan Gatul Betina Di Sungai Kendedes-Malang Sebagai “Candidate Animal Model” Dibidang Biologi Perkembangan - Vanda Aprinia Edfaniar; Benedictus Renaldi Ncemar; Winda Krisnawati; Nikmatul Iza (IKIP Budi Utomo Malang, 2022)
Gatul fish (Poecilia sp.) is included in the family Poeciliidae which is a small fish. This fish has the ability to breed very quickly, so the population of Gatul fish (Poecilia sp.) is very abundant. The purpose of this study was to determine the morphological characteristics of female Gatul fish in the Kendedes-Malang river as a